OWE-09 Outcomes of gut-focused hypnotherapy in school children and adolescents with severe refractory Irritable Bowel Syndrome. (June 2019) - Hasan, Syed S; Cruickshanks, Pamela; Whorwell, Peter J; Vasant, Dipesh H
Abstract : Introduction: Irritable Bowel Syndrome (IBS) symptoms in school children and adolescents are relatively common, often causing considerable embarrassment, social withdrawal, disruption to education and psychological distress. Pharmacological options in this group are limited due to safety concerns concerning antidepressants, making behavioural therapies such as gut-focussed hypnotherapy an attractive treatment option. Here, we evaluated outcomes from gut-focussed hypnotherapy in patients with IBS ≤ 18 years of age. Methods: Consecutive young patients (≤18 years of age) with severe IBS symptoms referred to our tertiary neurogastroenterology unit received 12 sessions of gut-focussed hypnotherapy at weekly intervals using the Manchester Protocol. All patients completed the Tellgen Absorption Scale before treatment and all completed the following measures before and after hypnotherapy; IBS symptom severity score (IBS-SSS), Hospital Anxiety and Depression scale (HADS), Non Colonic Symptom score and quality-of-life (QoL) score. Interference with education and the impact of hypnotherapy was also recorded. The primary outcome measure was response to hypnotherapy defined by a 50 point reduction in IBS-SSS. Data, expressed as mean ± standard error, were compared statistically before and after treatment using paired t-tests. Results: Young patients fulfilling Rome III diagnostic criteria for IBS ( n =26, median age 16 (range –8) years, n =17 (65%) female, mean duration of IBS 5.3 ± 0.9 years, n =11 IBS-D, n =6 IBS-C and n =9 IBS-mixed) completed the hypnotherapy programme. Mean baseline IBS-SSS was 321.5 ± 16.0. After hypnotherapy, n =23/26 (88%) responded, with an overall mean reduction in IBS-SSS of -160.9 ± 15.4 ( P <0.0001), and n =19/26 (73%) achieved the FDA recommended outcome of ≥30% reduction in abdominal pain scores. Hypnotherapy also improved; mean non-colonic symptom score by 102.1 ± 15.0 ( P <0.0001), mean HADS-anxiety by -3.0 ± 0.8 ( P =0.0007), mean HADS-depression by -2.1± 0.6 ( P =0.002), and improved mean QoL score by +89.7 ± 13.1 ( P <0.0001). Conclusion: These data, which form one of the largest reported series of gut-focussed hypnotherapy in children and adolescents with severe IBS, suggest that this treatment is even more effective in this group of patients than in adults. Hypnotherapy in severe childhood IBS patients may therefore have a role in preventing further suffering in adult life, reducing healthcare utilisation and related costs with wider socio-economic benefits. Furthermore, it allows many of them to return to full time education.